Making social sciences more scientific the need for predictive models - Taagepera, Rein (Oxford Oxford University Press, 2008)
In this book the author challenges the position of statistical analysis as the main quantitative tool used in social sciences. It will of interest to social science students, researchers, and methodologists.
Keywords: Social sciences -- Research; Social sciences -- Fieldwork; Social sciences -- Methodology; Sociology -- Methodology; Sociology -- Research; Data mining